Case Report: Peripheral combined central dual-target magnetic stimulation for non- motor symptoms of Parkinson’s disease - Li, Shangxiaoyue; Cai, Hongwei; Liao, Xiaoyu; Li, Aihong; Gu, Xiaosu; Guo, Aisong (Frontiers in Psychiatry, 2025)
This case report describes an innovative study using central combined vagus dual-target magnetic stimulation for treating non-motor symptoms of Parkinson’s disease (PD). PD is a common neurodegenerative disease, and almost all PD patients experience varying degrees of non-motor symptoms. However, there aren’t many targeted drugs for non-motor symptoms. Based on this clinical, we used left dorsolateral prefrontal cortex (DLPFC) and vagus nerve dual-target magnetic stimulation to treat PD non-motor symptoms. The choice of this combined stimulation method is based on the closed-loop rehabilitation theory of central-peripheral-central. Stimulation of DLPFC promoted the activation of brain functional areas and improved neuroplasticity, while stimulation of vagus nerve further enhanced the positive feedback and input to the central nervous system, forming a closed-loop information feedback, and synergically promoted the recovery of PD non-motor symptoms. The patient in this paper had non-motor symptoms such as constipation, short-term memory impairment, insomnia, depression, hallucinations. We had 10 sessions in total. The DLPFC stimulation was performed at 10Hz, 120% resting motor threshold (RMT) intensity, 1000 pulses per sequence for 10 minutes. The vagus nerve stimulation was performed at 10Hz, 100%RMT, with a total of 2000 pulses and a duration of 14 minutes. Assessment before treatment, after treatment, and at one month follow-up showed improvements in cognitive function, mood, and constipation symptoms. Therefore, we believe this treatment approach may represent a promising new option for treating non-motor symptoms of PD.